2016
DOI: 10.1590/1982-0216201618111915
|View full text |Cite
|
Sign up to set email alerts
|

Implicações da respiração oral na função pulmonar e músculos respiratórios

Abstract: The mouth breathing syndrome is characterized by a set of signs and symptoms, which may be present in subjects who replace an adequate and efficient nasal breathing mode by the mouth or mist breathing mode, for a period equal or superior of six months. The mouth or mist breathing mode may be associated to changes in the ventilatory function and mechanics. This review has the objective of investigating more deeply the consequences of the mouth breathing in the lung function and respiratory muscles, emphasizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
(44 reference statements)
0
9
1
12
Order By: Relevance
“…No changes were observed in the spirometric values of our sample; however, a literature review carried out by Veron et al 26 contrasts our findings by suggesting that disorders resulting from oral breathing contributes to muscle imbalance and poorer lung function. In another study, Trevisan et al 27 reported that mouth-breathing adults exhibit a reduction in diaphragmatic amplitude compared to nosebreathing adults, a result that is consistent with pulmonary restriction.…”
Section: Discussioncontrasting
confidence: 99%
“…No changes were observed in the spirometric values of our sample; however, a literature review carried out by Veron et al 26 contrasts our findings by suggesting that disorders resulting from oral breathing contributes to muscle imbalance and poorer lung function. In another study, Trevisan et al 27 reported that mouth-breathing adults exhibit a reduction in diaphragmatic amplitude compared to nosebreathing adults, a result that is consistent with pulmonary restriction.…”
Section: Discussioncontrasting
confidence: 99%
“…O inadequado desempenho da musculatura envolvida na respiração pode levar à diminuição da capacidade vital e do fornecimento de ar em nível glótico (Goffi-Fynn & Carroll, 2013;Traser et al, 2017). A região lombo-pélvica constitui o centro de força do corpo (CFC), uma cinta muscular que estabiliza a coluna e o tronco (Valente et al, 2015;Frigo & Braz, 2016;Santana, Prina, Albuquerque, Carvalho, & Caruso, 2016;Veron, Antunes, Milanesi, & Correa, 2016) e também auxilia a formação de pressão expiratória positiva para a fonação com a ativação conjunta dos músculos abdominais, do tronco e do assoalho pélvico (Cielo, Gonçalves, Lima, & Christmann, 2012;Lima, Cielo, & Christmann, 2016;Nunes, 2018;Pinto, Saraiva, Camatti, & Luz, 2018). O recrutamento da musculatura do CFC, a favor do trabalho respiratório (Valente et al, 2015;Frigo & Braz, 2016), permite melhora da atuação do diafragma e maior mobilidade da caixa torácica, podendo gerar maior fluxo aéreo expiratório e melhor qualidade da voz (Siqueira, Alencar, Oliveira, & Leite, 2014;Porolnik, Braz, Padilha, & Seidel, 2015).…”
Section: Introductionunclassified
“…Em indivíduos saudáveis, especificamente em crianças, como o caso da amostra estudada, é evidente que alterações posturais, hábitos de vida tecnológicos e pouca atividade física podem gerar comprometimentos respiratórios, ainda que sejam indivíduos considerados hígidos 3 . Dentre a principal alteração, encontra-se a respiração oral.…”
Section: Discussionunclassified